Sustainable management of intercropped vineyards on sandy acid soils - Cabras M.; Dettori D.; Mercenaro L.; Nieddu G.; Porqueddu C. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
A two-year experiment was carried out to study alternative systems of soil management and the possible effects on the grapevine. Conventional tillage was compared with legume cover crops based on subterranean clovers. Two different mixtures were utilized: Trifolium subterraneum cv Campeda (60%), T. brachycalycinum cv Antas (20%) and T. subterraneum cv Seaton Park (20%) in the first site and T. subterraneum cv Campeda (60%), T. brachycalycinum cv Antas (20%) and T. subterraneum cv Denmark (20%) in the second one. Data on seedling establishment and re-establishment, soil covering rate, canopy height, phenology of subterranean clover varieties, dry matter production were collected. Regarding grape vine, data on grape production and quality were recorded. The cover crops controlled the growth of weeds and ensured an excellent covering of the soil. No negative effects of cover crops on grape production and quality were observed in comparison with the tillage treatment.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)